A Ce-TiO 2 Preparation method of loaded oriented porous carbon aerogel
By preparing Ce-TiO2-loaded directional porous carbon aerogel, the problem of low photocatalytic CO2 reduction efficiency at this stage is solved, and stronger photoresponsiveness and better photocatalytic activity are achieved.
Patent Information
- Application Number
- CN202311406372.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-10-27
AI Technical Summary
At this stage, the photocatalytic CO2 reduction efficiency is low, the photoresponse range of traditional photocatalysts is limited, the photogenerated electron-hole is easy to recombinate, and the active sites are insufficient.
The preparation method of Ce-TiO2-loaded directional porous carbon aerogel is prepared by using the directional freezing process and sol-gel method, combined with CO2 supercritical drying and heat treatment process, Ce-TiO2 loads with high specific surface area and high porosity are prepared. Directional porous carbon aerogel.
The efficiency of photocatalytic CO2 reduction is improved, the photoresponse range is expanded, the photocatalytic activity is enhanced, and more reactive sites are provided.
Smart Images

Figure HDA0004516701180000011 
Figure HDA0004516701180000012
Abstract
Description
Technical Field
[0001] The invention belongs to the field of aerogel material preparation technology, and relates to a method for preparing Ce-TiO2 loaded oriented porous carbon aerogel, and in particular to a method for preparing Ce-TiO2 loaded oriented porous carbon aerogel by using oriented porous carbon as a carrier, preparing uniform chitosan aerogel through a oriented freezing process, and combining a sol-gel method, CO2 supercritical drying and a heat treatment process. Background Art
[0002] In recent years, as people continue to pay attention to environmental issues, CO2 emission reduction has gradually attracted people's attention. Therefore, CO2 photocatalytic reduction technology has received widespread attention.
[0003] Aerogel is a nanoporous material composed of nanoparticles. It has unique properties such as high specific surface area, high porosity and ultra-low packing density. It has received extensive attention in the fields of thermal insulation, adsorption, catalysis and sensing. The high specific surface area and highly interconnected pores of aerogel materials can expose more reactive sites. The small size effect of quantum mechanics shows that the energy level characteristics of the conduction band and valence band of nanomaterials are different from those of other materials. The separated energy levels formed by aerogels give them stronger redox capabilities. Therefore, aerogels are ideal photocatalytic carriers.
[0004] It is well known that the presence of carbon materials can promote the absorption of light by materials to a certain extent, convert light energy into heat energy, and accelerate chemical reactions. Chitosan is a natural polymer material and one of the most abundant renewable polymers on earth. Due to its special structural characteristics, its strong coordination and complexing ability can effectively separate photogenerated electrons and holes. There is an interaction between inorganic ions and organic matrices, so organic functional groups can be used to control the shape, size and spatial arrangement of inorganic materials. Tseng (Carbohydrate polymers, 2020, 230, 115584.) et al. have shown that the presence of hydroxyl and amino groups on chitosan substrates can fix nanoparticles and expand the visible light response range of materials. At the same time, the amino groups in the chitosan structural unit can react with CO2 to form carbamates, thereby enhancing the adsorption of CO2 by the material. In recent years, TiO2-based photocatalysts have been one of the photocatalysts currently synthesized on a large scale because of their suitable band gap, good optical activity and efficient light response ability. Liu (Journal of Alloys and Compounds, 2021, 861, 158598.) et al. evenly distributed nanorod-shaped TiO2 on the surface of rGO aerogels. The study found that the light response range of traditional TiO2 photocatalysts was successfully extended to the visible light region, while accelerating charge transfer, showing superior photocatalytic activity. Therefore, chitosan aerogels with porous structures and low prices are considered to be ideal carriers for regulating and fixing nanoparticles. Summary of the invention
[0005] The purpose of the present invention is to improve the current lack of photocatalytic CO2 reduction efficiency, the limitations of the light response range of traditional photocatalysts, the easy recombination of photogenerated electrons and holes, and the lack of active sites. A method for preparing Ce-TiO2 loaded directional porous carbon aerogel is provided. The method has simple raw materials and processes, low cost, and controllable structure. The prepared aerogel material has the characteristics of low density, high specific surface area and high porosity, and has positive production significance for realizing the application of aerogel materials in the field of catalysts.
[0006] The object of the present invention is achieved by the following method: a method for preparing Ce-TiO2 loaded oriented porous carbon aerogel, the specific steps of which are as follows:
[0007] (1) mixing chitosan powder, deionized water and acetic acid, and stirring the mixed solution at 10 to 70° C. until bubbles disappear to form a uniform chitosan solution;
[0008] (2) placing the chitosan solution obtained in step (1) in a mold, and obtaining chitosan aerogel after directional freeze-drying;
[0009] (3) a certain amount of titanium source, acid, Ce(NO3)3·6H2O and ethanol are mixed and stirred evenly for 10 to 60 minutes to obtain solution A;
[0010] (4) Mix a certain amount of ethanol and deionized water, stir evenly for 20 to 60 minutes to obtain solution B, and mix solution A and solution B and stir for 15 to 70 minutes;
[0011] (5) soaking the chitosan aerogel in step (2) in the mixed solution in step (4), allowing it to stand for gelation, and then allowing it to stand;
[0012] (6) immersing the chitosan aerogel obtained in step (5) in alcohol for aging, and then performing supercritical drying to obtain Ce-TiO2-loaded chitosan aerogel;
[0013] (7) The Ce-TiO2-loaded chitosan aerogel obtained in step (6) is placed in a muffle furnace for heat treatment for 5 to 9 hours to finally obtain a Ce-TiO2-loaded oriented porous carbon aerogel.
[0014] Wherein: in step (1), the mass ratio of chitosan, deionized water and acetic acid is (0.5-3.2): (0.8-9): 1, and the mass concentration of acetic acid is 2-10%; in step (3), the volume ratio of titanium source, acid, Ce(NO3)3·6H2O and ethanol is (0.3-3.1): (0.01-0.1): (0.2-4.2): 1; in step (4), the volume ratio of deionized water and ethanol is (0.5-5.8): 1, and the volume ratio of solution A to solution B is (0.5-3.3): 1.
[0015] Preferably, the mass concentration of acetic acid in step (1) is 2 to 10%.
[0016] Preferably, the titanium source in step (3) is a mixture of one or more of tetrabutyl titanate, titanium tetrachloride or isopropyl titanate.
[0017] Preferably, the acid in step (3) is a mixture of one or more of concentrated nitric acid (mass concentration 68-70%), concentrated sulfuric acid (mass concentration 96-99%) or concentrated hydrochloric acid (mass concentration 36-38%).
[0018] Preferably, the standing time in step (5) is 4 to 24 hours; and the number of aging times in step (6) is 4 to 7 times, with an interval of 5 to 8 hours between each time.
[0019] Preferably, the alcohol in step (6) is one of ethanol, methanol, acetone, ether, n-pentanol, isopropanol or a mixture thereof.
[0020] Preferably, the drying method described in step (6) is a carbon dioxide supercritical drying method: carbon dioxide is used as the drying medium, the reaction temperature is 40-80°C, the pressure in the high-pressure reactor is 8-12MPa, the degassing rate is 5-10L / min, and the drying time is 8-12h.
[0021] Preferably, the heat treatment temperature in step (7) is 400-700° C., and the heating rate is 2-10° C. / min.
[0022] Beneficial effects:
[0023] The method of the present invention and a Ce-TiO2-loaded oriented porous carbon aerogel material for photocatalytic CO2 reduction prepared by the method have the following characteristics:
[0024] (1) Compared with traditional TiO2 aerogels, Ce-TiO2-loaded oriented porous carbon aerogels have stronger light response ability and better photocatalytic CO2 reduction performance.
[0025] (2) The Ce-TiO2-loaded oriented porous carbon aerogel prepared in this method has high porosity and specific surface area, providing more reaction active sites for photocatalytic CO2 reduction.
[0026] (3) The Ce-TiO2-loaded oriented porous carbon aerogel material prepared by this method has a more uniform network skeleton structure, is cheap and environmentally friendly, and is in line with the concept of green chemistry development. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a physical picture of the bulk Ce-TiO2 loaded oriented porous carbon aerogel sample prepared in Example 1;
[0028] Figure 2 The yield graph of CH4 and CO from the photocatalytic CO2 reduction of Ce-TiO2-loaded oriented porous carbon aerogel prepared in Example 2; (a) CH4 and CO yield after 2 hours of illumination under full spectrum and (b) CH4 and CO yield after 2 hours of illumination under visible light. DETAILED DESCRIPTION
[0029] Example 1
[0030] Chitosan, deionized water and acetic acid (mass concentration 2%) were mixed in a mass ratio of 0.5:0.8:1 and stirred at 10°C until a uniform chitosan solution was formed. The chitosan solution was then placed in a mold and subjected to directional freeze drying to obtain chitosan aerogel. Tetrabutyl titanate, concentrated nitric acid (mass concentration 68%), Ce(NO3)3·6H2O and ethanol were mixed in a volume ratio of 0.3:0.01:0.2:1 and stirred evenly for 10 minutes to obtain solution A. Deionized water and ethanol were mixed in a volume ratio of 0.5:1 and stirred for 20 minutes to form solution B. Solution A and solution B were mixed in a volume ratio of 0.5:1 and stirred for 15 minutes to form a mixed solution. The chitosan aerogel was immersed in the mixed solution, allowed to stand for gelation, and then allowed to stand at room temperature for 4 hours, then immersed in ethanol for aging 4 times, each time with an interval of 5 hours, and then subjected to CO2 supercritical drying treatment, the reaction temperature was 40°C, the pressure in the autoclave was 8MPa, the degassing rate was 5L / min, and the drying time was 8h, to obtain Ce-TiO2-loaded chitosan aerogel. Finally, the obtained Ce-TiO2-loaded chitosan aerogel was placed in a muffle furnace for heat treatment for 5 hours, the heat treatment temperature was 400°C, and the heating rate was 2°C / min, and finally, Ce-TiO2-loaded oriented porous carbon aerogel was obtained. Figure 1 This is a physical picture of the Ce-TiO2-loaded oriented porous carbon aerogel prepared in Example 1. It can be seen from the figure that the prepared Ce-TiO2-loaded oriented porous carbon aerogel is in black block form. Under the condition of full spectrum irradiation for 2 hours, the production of CH4 reached 8.43μmol / (g·h) and the production of CO reached 38.69μmol / (g·h).
[0031] Example 2
[0032] Chitosan, deionized water and acetic acid (mass concentration 4%) were mixed in a mass ratio of 1.6:3.5:1 and stirred at 36°C until a uniform chitosan solution was formed. The chitosan solution was then placed in a mold and subjected to directional freeze drying to obtain chitosan aerogel. Tetrabutyl titanate, concentrated nitric acid (mass concentration 70%), Ce(NO3)3·6H2O and ethanol were mixed and stirred in a volume ratio of 1.3:0.03:1.7:1 for 29 minutes to form solution A, deionized water and ethanol were mixed and stirred in a volume ratio of 1.9:1 for 34 minutes to form solution B, and solution A and solution B were mixed and stirred in a volume ratio of 1.6:1 for 35 minutes to form a mixed solution. The chitosan aerogel was immersed in the mixed solution, allowed to stand for gelation, and then allowed to stand at room temperature for 9 hours, then immersed in methanol for aging 5 times, each time for 6 hours, and then subjected to CO2 supercritical drying treatment, the reaction temperature was 58°C, the pressure in the autoclave was 9.7MPa, the degassing rate was 6.8L / min, and the drying time was 9 hours, to obtain Ce-TiO2-loaded chitosan aerogel. Finally, the obtained Ce-TiO2-loaded chitosan aerogel was placed in a muffle furnace for heat treatment for 6 hours, the heat treatment temperature was 497°C, and the heating rate was 5°C / min, and finally, Ce-TiO2-loaded oriented porous carbon aerogel was obtained. Figure 2 This is the yield diagram of CH4 and CO in the photocatalytic CO2 reduction of Ce-TiO2 loaded oriented porous carbon aerogel prepared in Example 2. It can be seen from the figure that under the condition of full spectrum irradiation for 2 hours, the CH4 yield reaches 9.45μmol / (g·h) and the CO yield reaches 42.26μmol / (g·h).
[0033] Example 3
[0034] Chitosan, deionized water and acetic acid (mass concentration 7%) were mixed in a mass ratio of 2.4:6.2:1 and stirred at 51°C until a uniform chitosan solution was formed. The chitosan solution was then placed in a mold and subjected to directional freeze drying to obtain chitosan aerogel. Titanium tetrachloride, concentrated sulfuric acid (mass concentration 96%), Ce(NO3)3·6H2O and ethanol were mixed and stirred in a volume ratio of 2.3:0.07:2.8:1 for 45 minutes to form solution A, deionized water and ethanol were mixed and stirred in a volume ratio of 4.1:1 for 48 minutes to form solution B, and solution A and solution B were mixed and stirred in a volume ratio of 2.4:1 for 52 minutes to form a mixed solution. The chitosan aerogel was immersed in the mixed solution, allowed to stand for gelation, and then allowed to stand at room temperature for 18 hours. It was then immersed in ether for aging 6 times, each time with an interval of 7 hours, and then subjected to CO2 supercritical drying treatment. The reaction temperature was 71°C, the pressure in the autoclave was 10.4MPa, the degassing rate was 8.2L / min, and the drying time was 10 hours. Ce-TiO2-loaded chitosan aerogel was obtained. Finally, the obtained Ce-TiO2-loaded chitosan aerogel was placed in a muffle furnace for heat treatment for 9 hours. The heat treatment temperature was 600°C and the heating rate was 8°C / min. Finally, Ce-TiO2-loaded oriented porous carbon aerogel was obtained. Under the condition of full spectrum irradiation for 2 hours, the CH4 yield reached 7.46μmol / (g·h) and the CO yield reached 39.02μmol / (g·h).
[0035] Example 4
[0036] Chitosan, deionized water and acetic acid (mass concentration 10%) were mixed in a mass ratio of 3.2:9:1 and stirred at 70°C until a uniform chitosan solution was formed. The chitosan solution was then placed in a mold and subjected to directional freeze drying to obtain chitosan aerogel. Isopropyl titanate, concentrated hydrochloric acid (mass concentration 38%), Ce(NO3)3·6H2O and ethanol were mixed and stirred in a volume ratio of 3.1:0.1:4.2:1 for 60 minutes to form solution A, deionized water and ethanol were mixed and stirred in a volume ratio of 5.8:1 for 60 minutes to form solution B, and solution A and solution B were mixed and stirred in a volume ratio of 3.3:1 for 70 minutes to form a mixed solution. The chitosan aerogel was immersed in the mixed solution, allowed to stand for gelation, and then allowed to stand at room temperature for 24 hours. It was then immersed in acetone for aging 7 times, each time with an interval of 8 hours, and then subjected to CO2 supercritical drying treatment. The reaction temperature was 80°C, the pressure in the autoclave was 12MPa, the degassing rate was 10L / min, and the drying time was 12h to obtain Ce-TiO2-loaded chitosan aerogel. Finally, the obtained Ce-TiO2-loaded chitosan aerogel was placed in a muffle furnace for heat treatment for 8h, the heat treatment temperature was 700°C, and the heating rate was 10°C / min, and finally Ce-TiO2-loaded oriented porous carbon aerogel was obtained. Under the condition of full spectrum irradiation for 2 hours, the CH4 yield reached 8.67μmol / (g·h) and the CO yield reached 40.22μmol / (g·h).
Claims
1. A method for preparing Ce-TiO2-loaded oriented porous carbon aerogel, the specific steps of which are as follows: (1) Mix chitosan powder, deionized water and acetic acid, and stir the mixed solution at 10-70 °C until the bubbles disappear and a uniform chitosan solution is formed; (2) placing the chitosan solution obtained in step (1) in a mold, and obtaining chitosan aerogel after directional freeze-drying; (3) Mix a certain amount of titanium source, acid, Ce(NO3)3⋅6H2O and ethanol, and stir evenly for 10 to 60 min to obtain solution A; (4) Mix a certain amount of ethanol and deionized water, stir evenly for 20 to 60 min to obtain solution B, and mix solution A and solution B and stir for 15 to 70 min; (5) soaking the chitosan aerogel in step (2) in the mixed solution in step (4), allowing it to stand for gelation, and then allowing it to stand for a while; (6) soaking the chitosan aerogel obtained in step (5) in alcohol for aging, and then performing supercritical drying to obtain Ce-TiO2 loaded chitosan aerogel; (7) placing the Ce-TiO2-loaded chitosan aerogel obtained in step (6) in a muffle furnace and heat treating it at 400-700°C for 5-9h to finally obtain Ce-TiO2-loaded oriented porous carbon aerogel; in: In step (1), the mass ratio of chitosan, deionized water and acetic acid is (0.5-3.2): (0.8-9): 1, and the mass concentration of acetic acid is 2-10%; in step (3), the volume ratio of titanium source, acid, Ce(NO3)3⋅6H2O and ethanol is (0.3-3.1): (0.01-0.1): (0.2-4.2): 1; in step (4), the volume ratio of deionized water and ethanol is (0.5-5.8): 1, and the volume ratio of solution A to solution B is (0.5-3.3):
1.
2. The preparation method according to claim 1, characterized in that In step (3), the titanium source is a mixture of one or more of tetrabutyl titanate, titanium tetrachloride or isopropyl titanate.
3. The preparation method according to claim 1, characterized in that The acid in step (3) is a mixture of one or more of concentrated nitric acid, concentrated sulfuric acid or concentrated hydrochloric acid; wherein the mass concentration of concentrated nitric acid is 68-70%, the mass concentration of concentrated sulfuric acid is 96-99%, and the mass concentration of concentrated hydrochloric acid is 36-38%.
4. The preparation method according to claim 1, characterized in that The standing time in step (5) is 4 to 24 h; the number of aging times in step (6) is 4 to 7 times, with an interval of 5 to 8 h between each time.
5. The preparation method according to claim 1, characterized in that The alcohol in step (6) is one of ethanol, methanol, n-pentanol or isopropanol, or a mixture thereof.
6. The preparation method according to claim 1, characterized in that The supercritical drying treatment described in step (6) is a carbon dioxide supercritical drying method: carbon dioxide is used as the drying medium, the reaction temperature is 40~80°C, the pressure in the high-pressure reactor is 8~12 MPa, the degassing rate is 5~10 L / min, and the drying time is 8~12 h.
7. The preparation method according to claim 1, characterized in that The heating rate of the heat treatment in step (7) is 2-10 °C / min.
Citation Information
Patent Citations
Titanium dioxide supported type composite carbon aerogel as well as preparation and application thereof
CN108816259A
Preparation method of SiC-C composite aerogel for photocatalytic reduction of CO2
CN113996324A